The impact of banking risk management according to the project management approach on banking performance and the possibility of its application in Iraqi banks - an applied study of a sample of banks listed on the Iraqi Stock Exchange - Ali Ahmed Faris,; Russell Salih Mahdi, (Iraqi Journal for Administrative Sciences, 2024)
The study aimed at developing a framework for assessing the risk management of the project and how to implement it in order to improve the banking performance. The statistical and financial methods, which included the banking performance indicators, namely liquidity risk, interest rate risk, credit risk, capital risk, and profitability indicators, were measured by the return on assets, return on equity and return on deposits The sample was selected from 12 banks for the period from 2004 to 2016. The main conclusions of the study were that there is a great diversity in the risks faced by banks, which led to an urgent need to study these risks with a comprehensive perspective and abandon the traditional perspective that analyzes Each of the risks is separate from the other risks The study recommended the establishment of a specialized office to manage the risks of banks in a comprehensive manner without separating the types of risks and gives the office the authority to set policies to comply with the strategy of the bank in general .